Prevention of Congenital Cytomegalovirus Infection with Vaccines: State of the Art - Susanna Esposito; Giulia Chiopris; Giulia Messina; Tiziana D’Alvano; Serafina Perrone; Nicola Principi (Vaccines, 2021)
Cytomegalovirus (CMV) is the most common cause of congenital infection and non-genetic sensorineural hearing loss in childhood. Up to 2% of neonates, with the highest percentages found in developing countries, are congenitally infected with CMV. At birth, most of these infants are asymptomatic. However, approximately 10% have signs and symptoms of the disease, and 40–60% of symptomatic neonates will later develop permanent neurologic sequelae. To reduce congenital CMV (cCMV) infection, a vaccine able to prevent primary infection is essential. In this narrative review, actual ongoing research about the development of a CMV vaccine is discussed. The progressive increase in knowledge on the ways in which the host’s immune system and CMV relate has made it possible to clarify that the development of a vaccine that is certainly capable of reducing the risk of cCMV infection, and preventing both primary and nonprimary infections is extremely difficult. Many of the ways in which the virus evades the immune system and causes cCMV infection are not yet fully understood, especially in cases of nonprimary infection. Moreover, the schedule that should be recommended and that subjects must be vaccinated to obtain the greatest effect have not been precisely defined. Further studies are needed before the problem of cCMV infection and its related challenges can be totally solved.